2008
DOI: 10.1509/jmkr.45.5.575
|View full text |Cite
|
Sign up to set email alerts
|

To Innovate or Imitate? Entry Strategy and the Role of Market Research

Abstract: A firm planning market entry can attempt to develop a product that is either similar to the incumbent's existing offering (imitation) or entirely novel (innovation). The authors establish that when the incumbent is more aggressive in research and development (R&D), this negatively affects the entrant's marginal return on R&D. Thus, if greater profits produce a strong (weak) desire for the incumbent to increase its R&D level, the entrant will respond by sharply decreasing (increasing) its R&D le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 39 publications
(41 reference statements)
1
38
0
1
Order By: Relevance
“…Bundy et al 2013;Eesley and Lenox 2006;Kohli and Jaworski 1990). Interestingly, research has found that the information an organization gathers through market research may affect its decision to pursue a strategy of either innovation or imitation (e.g., Ofek and Turut 2008). This suggests that the way the organization responds to the knowledge gained through the different knowledge acquisition mechanisms varies in the degree to which its stakeholder practices are characterized as innovative or imitative.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Bundy et al 2013;Eesley and Lenox 2006;Kohli and Jaworski 1990). Interestingly, research has found that the information an organization gathers through market research may affect its decision to pursue a strategy of either innovation or imitation (e.g., Ofek and Turut 2008). This suggests that the way the organization responds to the knowledge gained through the different knowledge acquisition mechanisms varies in the degree to which its stakeholder practices are characterized as innovative or imitative.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…First, imitation allows the firm to react quickly to competitors' appealing products (Shenkar 2010b). Second, because the firm duplicates its rivals' products, it saves substantial resources in R&D, which often prove unrewarding (Ofek and Turut 2008;Shankar, Carpenter, and Krishnamurthi 1998). Third, by imitating competitors' products, the firm can learn from others' mistakes in product design and gain a better chance of success (Lieberman and Asaba 2006).…”
Section: Product Imitation and Performance Outcomesmentioning
confidence: 99%
“…In doing so, we highlight important boundary conditions for our findings and show that, when the product is nonsymbolic in nature or when little effort was expended to acquire the product, consumers for whom distinctiveness is particularly relevant do not exhibit negative reactions to being mimicked by a similar other Our final contribution lies in the broader focus of the research. Although work has examined consumer responses to marketers consciously imitating others' product offerings (Ofek and Turut 2008;Wariop and Alba 2004;Wilcox, Kim, and Sen 2009), to our knowledge, our research is the first to examine consumer reactions to being copied by another individual in their product choices.…”
mentioning
confidence: 99%